Musical texts and intertexts on the Archive of the Federico García Lorca Foundation: documental sources for researchers - Broullón Lozano, Manuel Antonio (Revista General de Información y Documentación, 2021)
The Archive of the Federico García Lorca Foundation (AFFGL) is the most important source for researchers on Lorca’s work. All kind of objects and documents have been conserved there: manuscripts, books, personal documents, letters, ephemera documents, etc. In this essay, sources related to music and Lorca’s musical activities shall be presented. We shall offer the enumeration and description of the materials found during the sessions of work developed at the Foundation on 2019. Specially, we will insist on documents that are not included on the oficial catalogue of the Archive, which may propose new information of interest for researches in the future.
Keywords: Federico García Lorca; Archive of the Federico García Lorca Researchers; Literature; Music; Silver Age